Agreement between ambulance and hospital records for information promoting urgent stroke treatment decisions. (February 2016) - Rudd, Matthew P.; Martin, Alexander J.; Harrison, Anne; Price, Christopher I.
Abstract : Objective: Rapid decision-making during acute stroke care can improve outcomes. We wished to assess whether crucial information to facilitate decisions is routinely collected by emergency practitioners before hospital admission. Materials and methods: We examined whether ambulance records contained information relevant to a thrombolysis treatment decision for consecutive stroke admissions to three emergency departments in England between 14 May 2012 and 10 June 2013. Results: In all, 424 of 544 (78%) records included a paramedic diagnosis of stroke. Twice as many hospital records contained a symptom onset time/last known to be well time, but there was 82% agreement within 1 h when a prehospital time was also recorded. This was more likely for younger patients. Documentation of medication history was infrequent (12%), particularly for anticoagulant status (6%). When compared with hospital documentation, paramedics recorded a history of diabetes for 38/49 (78%), previous stroke 44/69 (64%), hypertension 71/140 (51%) and atrial fibrillation 19/64 (30%). Conclusion: In a retrospective cohort of stroke patients admitted by emergency ambulance, standard practice did not consistently result in prehospital documentation of information that could promote rapid treatment decisions. Training emergency practitioners and/or providing clinical protocols could facilitate early stroke treatment decisions, but prehospital information availability is likely to be a limiting factor.